Paraplegia caused by cerebral contusions in the bilateral precentral gyri - Matsumura, Hideaki (Surg Neurol Int, 2016)
BACKGROUND: Paraplegia is mainly caused by spinal cord disease and rarely occurs due to head trauma. In this report, we describe a case of paraplegia caused by cerebral contusions in the bilateral precentral gyri. CASE DESCRIPTION: A 72-year-old man was admitted to our hospital with mildly impaired consciousness and severe pure motor paralysis in both legs. He was healthy until the morning of the day, but his wife found him injured in front of his house upon returning home. He had a subcutaneous hematoma in his occipital region, and seemed to have slipped by accident. Computed tomography of the brain and magnetic resonance imaging (MRI) of his spinal cord revealed no apparent cause of the paraplegia, although an MRI of his brain clearly revealed cerebral contusions in the bilateral precentral gyri. The cerebral contusion was diagnosed as the cause of pure motor paralysis of lower extremities. He received rehabilitation, and manual muscle testing of his legs revealed improvements. In the subacute phase, the precentral gyrus lesion disappeared on MRI. CONCLUSION: We must emphasize that cerebral contusion can be a differential diagnosis for paraplegia. In the acute phase, fluid-attenuated inversion recovery (FLAIR) MRI coronal and sagittal images are useful for identifying precentral gyri contusions. Paraplegia caused by a cerebral contusion may be misdiagnosed as a spinal concussion due to the disappearance of the precentral gyrus lesion on FLAIR MRI in the subacute phase.